State interference, para-politics and editorial control: the political economy of ‘Mirrorgate’ in Zimbabwe - Ureke, Oswelled (Intellect, 2016)
Publication by Mr Oswelled Ureke, Lecturer in the Department of Media and Society Studies, Midlands State University